Moral disengagement and associated processes in performance-enhancing drug use: a national qualitative investigation - Boardley, I. D.; Grix, J.; Dewar, A. J. (Journal of Sports Sciences, 2014)
This study investigated psychosocial processes associated with avoidance of health- and morality-based deterrents to performance-enhancing drug (PED) use. In-depth semi-structured interviews were conducted with 64 English male bodybuilders with experience of doping. Resultant data were content analysed deductively using definitions for the eight mechanisms of moral disengagement (MD; Bandura, A. (1991). Social cognitive theory of moral thought and action. In W. M. Kurtines & J. L. Gewirtz (Eds.), Handbook of moral behavior and development: Theory research and applications (pp. 71-129). Hillsdale, NJ: Lawrence Erlbaum Associates.), and three further themes from Boardley and Grix (2013. Doping in bodybuilders: A qualitative investigation of facilitative psychosocial processes. Qualitative Research in Sport, Exercise, and Health. Advance online publication, doi 10.1080/2159676X.2013.766809). These analyses evidenced six MD mechanisms, and all three of the themes from Boardley and Grix (2013. Doping in bodybuilders: A qualitative investigation of facilitative psychosocial processes. Qualitative Research in Sport, Exercise, and Health. Advance online publication). Subsequent frequency analyses revealed six of the eight MD mechanisms, and two of the three additional themes, were common across the sample. Overall, the findings suggest MD may help athletes circumvent health- and morality-based deterrents to doping, describe a process linking supplement and PED use and detail how some athletes may actively avoid social censure for doping by only discussing PED use with other PED users from within their training environment.